Pelestarian Nilai-Nilai dalam Tradisi Amuk-amukan Di Desa Padang Bulia Kecamatan Sukasada Kabupaten Buleleng - I Gede Arya Wiradnyana (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Bali is famous as an island with many unique traditions. The uniqueness of traditions found on the island of Bali is generally a legacy of the ancestors. The tradition contains the values that it wants to be inherited and should not be changed let alone abandoned. Values inthe tradition can be a guide in behaving for the people who own it. One of the traditions found in Bali is the ngamuk-amukan tradition in the village of Padang Bulia, Sukasada District. Tradition of ngamuk-amukan is traditions conducted in the village of Padang Bulia before the Nyepi celebration. This tradition is done as a symbol for human beings in implementing nyepi without having to hold the sense of resentment and anger. The ngamuk-amukan tradition is carried out by involving two people in a fight by blasting fire from danyuh which is burned. The ngamukamukan tradition contains religious values and social values. The religious value embodied in the ngamuk-amukan tradition is the belief that by doing this tradition it can eliminate all forms of anger and revenge ahead of the implementation of nyepi. In addition, this tradition is also believed to repel negative forces. While the social values that appear in the tradition are togetherness, self-control, and responsibility. In order to preserve the ngamuk-amukan tradition in the village of Padang Bulia, conservation efforts must involve all stakeholders in this case the provincial government, district or city government, and community who practice tradition.Keywords: Tradition, Value, Ngamuk-Amukan